Penggunaan Media Pembelajaran Inovatif Multiply Card pada Siswa Kelas IV di SDN Pamanuk 2 - Hasanah, Huswatun; Sari, Fitri Aida; Abadi, Ma'ulfi Kharis; Yanuar, Melinda; Firdaus, Firdaus (LPPM Universitas Bumigora, 2023)
Mathematical arithmetic operations skills, especially multiplication, are very important for students to be able to solve problems in their daily lives. The use of Multiply Card is a community service activity that aims to improve the learning outcomes of 4th grade students at SDN Pamanuk 2 who are still having difficulties with arithmetic operations, especially multiplication. The method of implementing this activity consists of several stages, namely planning, preparation, training, and evaluation. As a result, students were very enthusiastic in completing the preparation of this Multiply Card by remembering the answers to the multiplication questions. It can also improve students' numeracy skills, especially multiplication.